The Training of Canva-Based Interesting Learning Content Creation for Students at SMK Putra Anda Binjai - Prahmana, I Gusti; Tioria Pasaribu; Husnul Khair; Zira Fatmaira (CV. AFDIFAL MAJU BERKAH, 2024)
Technology is the main need in today's world of education because it is able to produce many applications that can be used as digital learning media. One of them is the Canva application which can be used to design learning displays or teaching materials as visual media in the teaching and learning process. This Community Service (PkM) aims to describe the training activities for creating interesting learning content with the Canva application for students at SMK Putra Anda Binjai which was held on March 15, 2024. The material of the training activities was delivered through presentations and questions and answers located in the Hall of SMK Putra Anda Binjai. This activity was carried out on the basis that most students still do not have insight and knowledge in developing and using applications that can be used in learning, lack of student creativity in designing innovative learning media in designing learning to be more interesting and fun, and students have difficulties in utilizing learning media applications, such as the Canva application, due to lack of information and training on the use of IT-based learning media. The methods used in this service are lectures, discussions, questions and answers, and finally evaluating activities using google forms. The result of this activity is that students have a broader knowledge of learning media, especially on the Canva application so that they are able to create learning content that is interesting, easy to understand, and fun.